Barriers to medication adherence in a rural-urban dual economy: a multi-stakeholder qualitative study - Xu, Jacqueline; Zhao, Mengxi; Vrosgou, Athina; Yu, Natalie Chin Wen; Liu, Chelsea; Zhang, Han; Ding, Chunxi; Roth, Noelle Wyman; Pan, Yuesong; Liu, Liping; Wang, Yilong; Wang, Yongjun; et al. (BMC health services research, 2021)
Background One of the most cost-effective treatments for secondary prevention of stroke and other non-communicable diseases is a long-term medication regimen. However, the complexities of medication adherence extend far beyond individual behavior change, particularly in low- and middle-income countries. The purpose of this study was to examine stakeholder perspectives on barriers to medication adherence for stroke patients in Beijing, China, identifying opportunities to improve care and policy in resource-constrained settings. Methods We conducted a qualitative, phenomenological analysis of data obtained from 36 individuals. Participants were patients; caregivers; healthcare providers; and representatives from industry and government, purposively selected to synthesize multiple perspectives on medication management and adherence for stroke secondary prevention in Beijing, China. Data was analyzed by thematic analysis across iterative coding cycles. Results Four major themes characterized barriers on medication adherence, across stakeholders and geographies: limitations driven by individual patient knowledge / attitudes; lack of patient-provider interaction time; lack of coordination across the stratified health system; and lack of affordability driven by high overall costs and limited insurance policies. Conclusions These barriers to medication management and adherence suggest opportunities for policy reform and local practice changes, particularly for multi-tiered health systems. Findings from this study in Beijing, China could be explored for applicability in other low- and middle-income countries with urban centers serving large geographic regions.